National and Alternative Reports on the Implementation of the European Social Charter (Revised) as a Principle of Human Rights Compliance - Yu. F. Ivanov; M. V. Ivanova (Law and Safety, 2025)
The article reveals the main provisions of the European Social Charter (revised) 1996 and its interconnection with the European Social Charter 1961. The research methodology is based on general scientific and special methods of cognition. It is emphasised that Ukraine's integration into the European legal space and the fulfilment of its obligations under the Association Agreement with the European Union require the harmonisation of national legislation with European standards. Emphasis is placed on the forms of control over the fulfilment of obligations under the Charters, including the submission of national reports and the collective complaint procedure. Complaints must raise general issues regarding the incompatibility of a law or practice with one or more provisions of the Charters and cannot be submitted in relation to individual situations. The procedure for reporting by participating states on the implementation of the provisions of the Charters is defined. The latest changes in the rules for submitting national reports are noted. States Parties that have not adopted the collective complaint procedure report on one group of provisions every two years, while those that have adopted the procedure report every four years. Reports should focus on the situation at the time of submission, as well as on actions taken or planned to improve the situation, and include information on the legislative framework, measures taken, and relevant indicators. A limited number of target questions are determined in advance, which must be answered in the report and which relate only to provisions adopted by the state. Emphasis is placed on the advantages of ratifying the Additional Protocol, which provides for a collective complaint system, to which Ukraine has not yet acceded. The functions of the main supervisory bodies of the Charters – the European Committee of Social Rights, the Governmental Committee of the European Social Charter and the European Code of Social Security – are identified, as well as the role of the Committee of Ministers and the Parliamentary Assembly of the Council of Europe in the procedure for assessing the implementation of the Charters. Three main stages in the reporting procedure have been established: examination of reports on compliance/non-compliance with the Charters; adoption of conclusions (making recommendations if necessary); consideration of the recommendations made. Emphasis is placed on the mechanism for submitting comments on national reports (alternative reports), which may contain additional or alternative information on all issues raised in the national report, or comment on a single issue or information that is missing from the government report. The role of the Ukrainian Parliament Commissioner for Human Rights in the process of reporting on the implementation of the provisions of the Charters was highlighted.